Histopathologic Characteristics of Idiopathic Granulomatous Mastitis (11 Cases) - Lebe, Banu; Tuna, Burcin; Kirimca, Feza; Canda, Tulay (Annals of Medical Research, 2021)
None
Keywords: Breast, Mastitis, Idiopathic Granulomatous, Histopathology.